A Gas Diffusion Layer Impregnated with Mn3O4‐Decorated N‐Doped Carbon Nanotubes for the Oxygen Reduction Reaction in Zinc‐Air Batteries. Issue 10 (26th August 2019) - Aasen, Drew; Clark, Michael; Ivey, Douglas G.
Abstract: Mn3 O4 ‐decorated N‐CNTs are synthesized and impregnated into porous carbon paper (gas diffusion layer or GDL) to form a composite catalyst‐GDL material in a simple and novel one‐pot process. The impregnated electrode features high active surface area, improved discharge performance, and reduced vulnerability to flooding when compared with other electrode preparation techniques for similar catalysts. Electrochemical and battery testing show catalytic activity and a maximum discharge potential superior to other CNT supported Mn3 O4 catalysts, and comparable to commercially used Pt−Ru (1.21 V at 20 mA cm −2 ). The composite is cycled at 10 mA cm −2 and 20 mA cm −2 as a bifunctional catalyst and as an oxygen reduction reaction (ORR) exclusive catalyst, respectively. Discharge performance is stable over 200 cycles at 20 mA cm −2 when used exclusively for ORR with a discharge‐charge efficiency superior to Pt−Ru when coupled with electrodeposited Co−Fe as the OER catalyst (efficiency of 59 % after cycling). Abstract : Stop the flood : A gas diffusion layer (GDL) impregnated with Mn3 O4 ‐decorated N‐CNTs catalysts is used as an oxygen reduction reaction (ORR)‐active electrode for Zn‐air batteries. The impregnated electrode increases surface area and helps to prevent the loss of the three‐phase boundary between O2, catalysts, and electrolyte during cycling. The simple and scalable impregnation technique consistently enabled high performance ORR electrodes for Zn‐air batteries.